Numerical Modeling of Sediment Transport Rate and Shoreline Changes of Jazireh-e Shomali-Jonoubi Port in the Persian Gulf - Milad Bamdadi Nejad; Mohammad Javad Ketabdari; Farhad Shojaei (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
Studying the sediments and predicting the coastal morphological changes have wide applications in coastal engineering, including coastal management, operation, and design of the structures as well as their maintenance, development, and expansion of coasts and coastal structures, which are of paramount importance. This study aims to model the shoreline changes around the Jazireh-e Shomali-Jonoubi Port, calculate the amount of advancement and recession due to the construction of the breakwater, and to determine the areas exposed to erosion and sedimentation. To this end, a series of primary information, including aerial and satellite images, hydrographic and topographic maps, and the specifications and grading of the sediment of the considered coast, has been collected and the overall morphology of the area has been determined. The input data into the model include a 12-year time series of the wave (height, period, and direction of the wave) and the wave climate. The length of the shoreline is 4 km and a profile perpendicular to the coast with a length of 1500 m has been applied to the model. Finally, using numerical modeling, the net and gross potential rates of annual and cumulative sediment transport, as well as shoreline changes after 12 years, were simulated. The effect and length of sedimentation behind the port’s breakwater after 1, 5, 10 and 12 years are 81, 190, 247 and 267 meters, respectively, which is in good agreement with the actual observations. Because the length of the breakwaters is 300 meters, the sedimentation problem has not yet been established for the port after 12 years.